Youubi gamer: desenvolvimento e avaliação de uma aplicação baseada em gamificação e geolocalização - Oliveira, Everton Jales de (Universidade Federal Rural do Semi-Árido, 2017)
The goal of ubiquitous computing is the contextual integration of computing systems into people's activities and interests in a transparent, natural, and continuous way. Although the concept of ubiquitous computing is not yet a reality, it is possible to observe the increasing popularization of digital devices interconnected with people's daily lives. This perspective makes it possible for people to produce and disseminate information easily, quickly, and conveniently, according to their needs and interests. Thus, this scenario also potentialize the emergence of new teaching-learning practices, which can occur in any time and space, not limited to the walls and activities imposed by educational institutions, which gives rise to the concept of ubiquitous learning. In this scenario, integrating gamification techniques in a ubiquitous learning application, contribute to increase the motivation of the learners in the construction and dissemination of knowledge. In this way, the goal was to design, develop and evaluate an application that uses elements of u-learning that integrates elements of gamification, called here Youubi Gamer, making use of the services of the Youubi API, and analyzing the impacts on the practices and strategies of learning adopted by its users. To reach the established goal, the method was divided into two phases. In the first phase was used the design thinking, composed in four stages. Immersion, brainstorming of ideas, prototyping and implementation. In the second phase of the method, qualitative and quantitative data collection techniques are used, such as the application of a profile questionnaire, satisfaction questionnaire, diaries, and focus group. As a result of the work we have the application Youubi Gamer that was evaluated during the period of one week in a higher education institution. After collecting and analyzing the data, the introduction of Youubi Gamer revealed the emergence of new learning practices by the students, and an increase in their engagement according to the gamification elements present in the application.
Monografia
Keywords: Aprendizagem ubíqua; Gamificação; Geolocalização; Dispositivos móveis; Ubiquitous learning; Gamification; Geolocation; Mobile devices; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO